Pro Social Behavior dalam Animasi Upin & Ipin Membangun Pendidikan Karakter yang Selaras dengan Nilai-Nilai Islam - Salsabila Hady Ningsih; Alya Fitriani; Surawan Surawan (Cakrawala: Journal of Religious Studies and Global Society, 2025)
Character education is a form of human activity in which there is an educational action intended for the next generation, which in spreading it in this era can use the media. In this modern era, media has a great influence on the way children learn when imitating social behavior. One effective way is to use animation that can help children understand and model good behavior in an interesting and easy-to-understand way. One animation that can help children imitate social behavior is Upin & Ipin, which contains various prosocial behaviors. This makes Upin & Ipin cartoons a potential medium in conveying character education messages that are in line with Islamic values. The method used in this research is library research. The results showed a discussion by taking three episodes of Upin & Ipin animation, namely: Rumah Rasa Sayang, Ijat Sudah Berani Naik Sepeda and Gerobok Rezeki, where these three episodes contain pro-social behavior values in building childrens character education that is in line with Islamic values. The conclusion is that character education can be built through children's animated shows such as Upin & Ipin which contain various pro-social behaviors that are easy for children to imitate and understand.